2020
DOI: 10.3390/ma13184156
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Triboelectric Performance of Modified PDMS Nanocomposite Multilayered Nanogenerators

Abstract: Recently, triboelectric nanogenerators (TENGs) have been widely utilized to address the energy demand of portable electronic devices by harvesting electrical energy from human activities or immediate surroundings. To increase the surface charge and surface area of negative TENGs, previous studies suggested several approaches such as micro-patterned arrays, porous structures, multilayer alignment, ion injections, ground systems and mixing of high dielectric constant materials. However, the preparation processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…Few studies have focused on TMs assembled via the layer-by-layer (LbL) method, and several studies have reported some results that can be classified as LbL-assisted TMs, such as the surface modification of negative TMs for high humidity resistance TENG devices or metal-like conductive elastomer positive TMs . However, these required additional processing for use as a TENG device, showing a relatively low TENG output performance at a large contact load of approximately 90 N. This was not desirable for TENG applications; thus, our group has adopted a facile and inexpensive LbL assembly process that allows the production of ultra-thin films that can be coated on any structural surface. , We thus designed and fabricated a poly­(vinyl alcohol) (PVA) and graphene nanoplatelet (GNP)-dispersive poly­(4-styrene-sulfonic acid) (PSS) bilayer (BL) film (denoted as [PVA/GNP-PSS] n ) as both an electrode and an electron donor. , The [PVA/GNP-PSS] 3 film-based TENG showed a good performance of ∼100 V and ∼4 μA. However, it still needs to be improved due to its low affinity to donate electrons (i.e., a high work function of ∼4.98 eV) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have focused on TMs assembled via the layer-by-layer (LbL) method, and several studies have reported some results that can be classified as LbL-assisted TMs, such as the surface modification of negative TMs for high humidity resistance TENG devices or metal-like conductive elastomer positive TMs . However, these required additional processing for use as a TENG device, showing a relatively low TENG output performance at a large contact load of approximately 90 N. This was not desirable for TENG applications; thus, our group has adopted a facile and inexpensive LbL assembly process that allows the production of ultra-thin films that can be coated on any structural surface. , We thus designed and fabricated a poly­(vinyl alcohol) (PVA) and graphene nanoplatelet (GNP)-dispersive poly­(4-styrene-sulfonic acid) (PSS) bilayer (BL) film (denoted as [PVA/GNP-PSS] n ) as both an electrode and an electron donor. , The [PVA/GNP-PSS] 3 film-based TENG showed a good performance of ∼100 V and ∼4 μA. However, it still needs to be improved due to its low affinity to donate electrons (i.e., a high work function of ∼4.98 eV) .…”
mentioning
confidence: 99%
“…33,34 We thus designed and fabricated a poly(vinyl alcohol) (PVA) and graphene nanoplatelet (GNP)-dispersive poly(4-styrene-sulfonic acid) (PSS) bilayer (BL) film (denoted as [PVA/GNP-PSS] n ) as both an electrode and an electron donor. 35,36 The [PVA/GNP-PSS] 3 film-based TENG showed a good performance of ∼100 V and ∼4 μA. However, it still needs to be improved due to its low affinity to donate electrons (i.e., a high work function of ∼4.98 eV).…”
mentioning
confidence: 99%
“…(c) GNP-PDMS preparation process. Reproduced with permission from ref . Copyright 2020, Multidisciplinary Digital Publishing Institute.…”
Section: Increasing Charge Densitymentioning
confidence: 99%
“…The surface characteristics, such as surface area and topography, of the contact layer are key to improving the triboelectric effect induced by the contact between layers. In this sense, some studies seek to modify the surface of contact materials using chemical 120,121 or physical treatments. 122 Interestingly, Qi et al 94 opted for the fabrication of a nanofibrous and stretchable polyamide 6 (PA6) contact layer prepared by electrospinning (Figure 6A).…”
Section: Performance Of Hydrogel-based Tengsmentioning
confidence: 99%